Peran Home Library dalam Meningkatkan Literasi Anak (Studi Home Library Dosen di Universitas Muhammadiyah Mataram) - Rohana, Rohana (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
The existence of a home library in every family provides easier and guaranteed access to information from information that isn’t needed, can grow and develop children's reading interest and culture from an early age, and develop positive brushes and develop children's skills through quality reading. In the context of the Covid 19 pandemic, home libraries are a good alternative in improving children's literacy. This study aims to determine the role of the home library in improving children's literacy (study at Muhammadiyah University of Mataram). The research method uses a qualitative approach. Sources of data obtained through primary sources (direct informants) and secondary sources (books or journals) related to the research. The data collection procedure was carried out by observation, interviews, and documentation. The collected data were analyzed and interpreted. The results showed that the home library plays a role in growing and improving children's literacy such as reading, writing and arithmetic literacy. children's character literacy such as discipline, honesty, responsibility, manners, mutual love, and respect for each other .The role of the home library, among others; first, the home library as a source of children's reading. Second, as a child's learning media. Third, as a place for children's recreation. Fourth, as a medium for children's cultural education. And fifth, as a medium for children's character education.